A Feasibility and Acceptability Trial of Social Cognitive Therapy in Early Psychosis Delivered Through a Virtual World: The VEEP Study - Thompson, Andrew; Elahi, Farah; Realpe, Alba; Birchwood, Max; Taylor, David; Vlaev, Ivo; Leahy, Fiona; Bucci, Sandra (Frontiers in Psychiatry, 2020)
Background: Addressing specific social cognitive difficulties is an important target in early psychosis and may help address poor functional outcomes. However, structured interventions using standard therapy settings including groups suffer from difficulties in recruitment and retention. Aims: To address these issues, we aimed to modify an existing group social cognitive intervention entitled ‘Social Cognition and Interaction Training’ (SCIT) to be delivered through a virtual world environment (Second Life ). Methods: A single arm non-randomised proof-of-concept trial of SCIT-VR was conducted. Five groups of 3-5 individuals per group were recruited over 6 months. Eight sessions of SCIT-VR therapy were delivered through the virtual world platform Second Life over a 5-week intervention window. Feasibility was examined using recruitment rates and retention. Acceptability was examined using qualitative methods. Secondary outcomes including social cognitive indices, functioning and anxiety were measured pre- and post-intervention. Results: The SCIT-VR therapy delivered was feasible (36% consent rate and 73.3% intervention completion rate), acceptable (high overall post-session satisfaction scores) and safe (no serious adverse events) and had high levels of participant satisfaction. Users found the environment immersive. Pre-post changes were found in emotion recognition scores and levels of anxiety. There were no signs of clinical deterioration on any of the secondary measures. Conclusion: This proof-of-concept pilot trial suggested that delivering SCIT-VR through a virtual world is feasible and acceptable. There were some changes in pre-post outcome measures that suggest the intervention has face validity. There is sufficient evidence to support a larger powered randomised controlled trial.